PHENOLOGY AND FEATURES OF THE SPREAD OF PESTS OF SORGHUM IN THE FOREST-STEPPE OF UKRAINE - Іванова, К. О. (Scientific Progress & Innovations, 2017)
The article describes the features formation of the modern structure of the sorghum entomological complex. The dominant and most harmful insect species on sorghum crops have been found. The biology and phenology of the main pests of sorghum, which were observed in the research area, were specified. The current state and prospects of introduction of the newest technologies of sorghum protection in the Forest-Steppe have been analyzed. The time and the period of reproduction and distribution of individual pests species and their harmfulness to sorghum are estimated. Indicators of sorghum hybrids stability to a complex of harmful insects of the Forest-Steppe of Ukraine are determined.